The impact of team cohesion on athlete engagement in collegiate basketball leagues: the moderating role of paternalistic leadership - Wang, Liang; Xu, Jianhua; Liu, Yao (Frontiers in Psychology, 2024)
Objective This study investigates the impact of team cohesion on the engagement of college basketball players, and examines the moderating effects of authoritarian, benevolent, and moral leadership styles within paternalistic leadership on this influence. This provides theoretical insights for improving athlete engagement. Methods Data from 404 athletes participating in the 26th China Collegiate Basketball League were collected through a questionnaire survey and analyzed statistically. Results (1) Team cohesion has a significant positive impact on athlete engagement in collegiate basketball players. (2) Authoritarian leadership has a significant negative moderating effect on the relationship between team cohesion and athlete engagement in collegiate basketball players; the stronger the authoritarian leadership, the weaker the positive impact of team cohesion on athlete engagement in collegiate basketball players. This effect diminishes and becomes statistically insignificant when the authoritarian leadership score exceeds 5.88. (3) Benevolent leadership does not have a significant moderating effect between team cohesion and athlete engagement in collegiate basketball players. (4) Moral leadership has a significant positive moderating effect on the relationship between team cohesion and athlete engagement in collegiate basketball players; the higher the moral leadership, the stronger the positive impact of team cohesion on athlete engagement in collegiate basketball players, which becomes insignificant when the moral leadership score is below 2.75. Conclusion Enhancing team cohesion is an effective method to increase athlete engagement in collegiate basketball players. It is advisable for collegiate basketball coaches to refrain from adopting controlling and demeaning authoritative approaches, and instead, emphasize ethical leadership practices, continually enhancing their own abilities and virtues to serve as role models.